Structural Characterization of Sulfated Polysaccharide Isolated From Red Algae (Gelidium crinale) and Antioxidant and Anti-Inflammatory Effects in Macrophage Cells - Pei, Yu; Yang, Shengtao; Xiao, Zhenbang; Zhou, Chunxia; Hong, Pengzhi; Qian, Zhong-Ji (Frontiers in Bioengineering and Biotechnology, 2021)
Gelidium crinale, the red algae belong to Geliaceae Gelidium, is a traditional edible and industrial algae in China. A sulfated polysaccharide (GNP) successfully separated from Gelidium crinale by acid extraction and two step column chromatography. The chemical analysis showed that the molecular weight of GNP was 25.8 kDa and the monosaccharide composition had the highest galactose content. And confirmed that the presence and content (16.5%) of sulfate with fourier transform infrared spectroscopy (FT-IR) spectrometer and barium chloride-gelatin methods. In addition, the effect of GNP on lipopolysaccharide (LPS)-induced oxidative stress and inflammation in macrophages was also evaluated. The research results showed that GNP had fairly strong scavenging activities on 2, 2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical, hydroxyl radical and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, and had Fe2+ chelating ability in dose-dependent manner. At the same time, it significantly inhibits the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) and the production of pro-inflammatory cytokines in RAW 264.7 cells induced by LPS through blocking mitogen-activated protein kinase (MAPK)/nuclear factor kappa beta (NF-κB) signaling pathway. These results indicate that GNP may be a latent component anti-inflammation in the pharmaceutical and functional food industries.